Synthesis and characterization of CuO nanofibers, and investigation for its suitability as blocking layer in ZnO NPs based dye sensitized solar cell and as photocatalyst in organic dye degradation - Sahay, Rahul (2012)
Electrospun copper based composite nanofibers were synthesized using the copper acetate/polyvinyl alcohol/water solution as starting material. Synthesized composite nanofibers were sintered at 500 °C to obtain CuOnanofibers. XRD, FTIR and XPS techniques were used to confirm the presence of pure CuO nanostructures. The effect of annealing cycle on the crystalline structure of the CuOnanofibers was analyzed and observed that the decrease in crystallite size with an increase in the dwelling time improved the orientation of the CuO crystallite. The blue-shift in the band-gap energies of CuOnanofibers was observed as a result of quantum confinement from bulk CuO (1.2 eV) to one dimensional (1D) nanostructures (∼1.746 eV). The catalytic activity of the CuO fibers for the degradation of methyl orange was carried out and as a blockinglayer in ZnObased DSSC was fabricated and observed a ∼25% increase in the current density.